Field and Laboratory Investigation of a 60-Year-Old Precast Prestressed Concrete Building in Japan - Kamaruddin, Nadia; Raouffard, Mohammad Mahdi; Nishiyama, Minehiro (International Journal of Sustainable Construction Engineering and Technology, 2023)
In Japan, the application of the prestressed concrete (PC) system has become quite popular, especially in bridge and building constructions. Since it was first introduced in the early 1950s, the number of buildings using the PC system has substantially increased. However, following a certain period in the service life of the PC system, the serviceability of such structures especially following an earthquake has become a primary concern, especially when exposed to severe corrosion-prone environments. In this research, the City Hall building of Nandan Town, Awaji Island in Japan, was chosen to investigate the influence of corrosion on the durability of the building structure, which was initially constructed in 1957 as the first building that used PC members for beams. This paper describes the building and results of the field crack inspection and corrosion test results on concrete core samples from the building. Accordingly, the study found that the building had material deteriorations due to its corrosive surrounding environment and severe damage on the concrete cover of the PC anchorage.